KAMPANYE ANTIMICROBIAL RESISTENCE (AMR) PADA IBU-IBU DASA WISMA KWARASAN, SLEMAN - Cahyo Wibisono; Alfian Yusak Muzaki; Anggi Muhtar Pratama (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2022)
Antimicrobial Resistance (AMR) is a serious problem and is still widely ignored by the wider community, including in the community of Kwarasan Hamlet, Gamping District, Sleman Regency, Yogyakarta. AMR is a condition in which the drugs given are ineffective and even unable to eradicate microbes as disease agents such as bacteria. AMR can be caused by the unwise use of antibiotics. The state of AMR makes infectious diseases such as tuberculosis difficult to cure. Knowledge about AMR is important to be disseminated and understood to the public. It is proven in the records of the Gamping I Health Center for the last 5 years that the level of antibiotic use in Kwarasan Hamlet has reached 90%. Besides that, there have also been 116 cases of tuberculosis, some of which ended in death. The women of Dasa Wisma Melati Dusun Kwarasan are very enthusiastic about understanding and campaigning for knowledge about AMR to the wider community. Based on this potential, Dusun Kwarasan can become a pioneer in health care through the Antimicrobial Resistance (AMR) campaign program. This program is structured with the flow of counseling program deliberation, preparation of extension programs, counseling on AMR, formation of AMR cadres, upgrading of AMR cadres, action plans for AMR cadres and program evaluation. The program will support the realization of a community that cares about AMR, prevents infectious diseases caused by microbes that are difficult to cure and becomes a pioneer in AMR care.